Crimes incidence and control in an academic library: implications for management and policy (2010)
The study investigated the incidence and control of crimes in Kenneth Dike library, university of Ibadan, Nigeria. Observation and survey research techniques were used to obtain data for the study. 120 copies of questionnaire developed were administered to the different categories of workers in the library, because the responsibility for effective security is collective and not exclusive to any particular individual or group within the library. Out of these, 102 were returned, while 100 were validly completed, thus giving a response rate of 83.3 percent. The findings reveal that inadequate staff, lack of proper supervision, non availability of photo-coping machines, amongst others are the reason for prevalence of criminal activities in the library. The study has established the prevalence of criminal activities and offer some suggestions on how to combat and reduce the incidence of crimes in a library.